Dynamic Privacy Policies with Multiple Contexts - BILJALI, ARBNOR; HUSKAJ, VALON (My University, 2020)
Privacy polices are widely used on Social Network Services(SNS) in order to limit the audience on certain information posted on the SNS. In this master thesis we are concerned with the problem of defining dynamic privacy policies with regards to multiple contexts such as time and location on multiple SNS simultaneously. For that we have designed and implemented an application to evaluate the thesis work. Our results show that it is possible to use a centralized client application to send content towards multiple SNS simultaneously. This due to the design of an architec ture that allows multiple integration of SNS on the same application. Another result of the contributing architecture is the support of one, two or more contexts in the same dynamic privacy policy. This is possible because of the contextual information, such as GPS location etc, derived from the client device itself.
Keywords: Privacy policy; Dynamic privacy policy; Social Network; Conditional policies; Contextual information